IDENTIFICATION OF ATSIRI OIL COMPONENTS IN SPICES COFFEE USING KG S - Fenti Fatmawati (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2018)
Spice coffee is a blend of arabica and robusta coffee bean by using the addition of spice such as ginger, red ginger, galingale, black paper, cardamom, cumin and cinnamon. Spice coffee is intended to improve the taste of fresh coffee and warm. This study aims to determine the essential oil component in spice coffee. Identification of essential oil components has been done by using Gas Chromatography Spectrometry Mass (GC-MS) method in spice coffee produced from 3 cities Bandung, Surabaya and Malang. The first step was sample preparation using vapor distillation and extraction with solvent. The second step was to identify essential oil components in the sample using the GC- MS method. The result of identification essential oil component in spice coffee showed that in sample A had 3 main components identified as Phenol,nonyl (53.40%), 4-Azido-Phenol 18.70%) and Caffeine (98.40%), sample B has 4 main components identified as γ-Terpinene (32.80%), Linalool (43.20%), α-Terpineol (30.30%) and Caffeine (98.40%), sample C has 7 main components identified as Linalool (53.4%), 4-Terpineol (55.0%), α-Terpineol (32.9%), Cinnamyl alcohol (78.2%), α-Curcumene (84.2%), Caffeine (98.3%) and Gingerol (93.7%). Key words: Coffee, Essential oil, Spice.